2010
DOI: 10.1007/s00432-010-0786-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and metastatic value of phosphatase of regenerating liver-3 in invasive breast cancer

Abstract: These results strongly suggest that PRL-3 expression can indicate the potential role of LNM to some extent. Increasing the risk of tumor metastasis (OR = 3.889). Our results also imply that PRL-3 might be a novel molecular marker for predicting relapse of invasive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Previous studies have reported PTP4A3 overexpression in several cancers, including breast, gastric and colon cancer (23,24), particularly with metastatic colon and breast cancer. Furthermore, PTP4A3 expression is higher in invasive cancer than normal breast tissue, and protein expression is associated with lymph node positivity (25), as well as reduced disease-free survival (23). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported PTP4A3 overexpression in several cancers, including breast, gastric and colon cancer (23,24), particularly with metastatic colon and breast cancer. Furthermore, PTP4A3 expression is higher in invasive cancer than normal breast tissue, and protein expression is associated with lymph node positivity (25), as well as reduced disease-free survival (23). …”
Section: Discussionmentioning
confidence: 99%
“…For example, in carcinoma cell lines PTP4A3 expression may lead to down regulation of p53 [18] and it is variably induced by γ-irradiation [19]. Finally, high PTP4A3 expression has been linked to increased tumor aggressiveness in different types of solid tumors, e.g., melanoma, gastric cancer, colon cancer, hepatocellular carcinoma and breast cancer [20], [21], [22], [23], [24], possibly because high PTP4A3 expression leads to increased epithelial-mesenchymal transition [25].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al found the opposite to be true, where PRL-3 overexpression was associated with reduced the life span of node-negative patients but not node-positive patients (23). Furthermore, a recent study by Hao et al found PRL-3 overexpression in the primary tumor to be significantly correlated with breast cancer metastasis to the lymph node, while Wang et al and Radke et al reported that lymph node metastasis was independent of PRL-3 expression in the primary tumor (12,23,24). Further studies will be required to reconcile these conflicting results.…”
Section: Role Of Prl In Cancermentioning
confidence: 99%